Aboriginal watercraft on the Pacific coast of SouthAmerica (2022)
eng: This study by Clinton Edwards is by far the best and most systematic treatment of ancient Andean boating which has been undertaken. The subject is an important one, because many hypotheses, both of diffusion and of independent invention, depend on its results. Edwards’ review of the early colonial literature seems to be both exhaustive and definitive, and I feel that he has settled a number of questions which have long been the subject of debate. He shows convincingly that sails were used aboriginally on the balsa rafts of Guayaquil, and that these sails were not square-rigged or standard European lateen-rigged, but were rather triangular sheets lashed to curved, two-piece masts of a non-European type. He shows, too, that craft capable of long sea voyages (sailing rafts and dugout canoes) were in use only on the Colombian, Ecuadorian, and northernmost Peruvian coast, not along the main part of the Peruvian coast which is associated with the ancient pre-Inca civilizations.